Implementation of Agrarian Reform On Assets And Equitable Access To Reform In Batu City - Nurul Salsabila Hadiyanti; Imam Koeswahyono; Ngesti Dwi Prasetyo (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
Agrarian reform is a strategic state policy aimed at realizing agrarian justice through the restructuring of land control, ownership, use, and utilization accompanied by community empowerment as the subject of agrarian reform. However, the implementation of agrarian reform at the local level, including in Batu City, faces various challenges, particularly in integrating asset reform and access reform as well as pressures arising from land commercialization driven by tourism and investment development. This study aims to analyze the effectiveness of the integration between asset reform and access reform in the implementation of agrarian reform policies in Batu City and to examine the impact of land commercialization on the sustainability of agrarian reform. This research uses a normative juridical method with statutory and conceptual approaches supported by empirical analysis. The legal materials consist of laws and regulations related to agrarian reform, regional policies, and relevant literature, which are analyzed through qualitative legal analysis. The results of this study indicate that the integration between asset reform and access reform in Batu City has not been implemented optimally. The implementation of agrarian reform still tends to focus on asset legalization, while access reform, including economic empowerment, institutional strengthening, and sustainable land tenure protection, has not been systematically implemented. In addition, the increasing commercialization of land through spatial planning policies and investment permits has limited the space for agrarian reform and increased the vulnerability of agrarian communities. Therefore, strengthening local policy strategies, including the reorientation of spatial planning based on agrarian reform, the strengthening of regional regulations, and the integration of agrarian reform with local economic development, is necessary to achieve sustainable and inclusive agrarian reform.